Design and control of mobile third arm assistive cobot for heavy object manipulation - Tan, Ting Hao (Nanyang Technological University, 2022)
Manual handling is currently one of the leading causes of injuries among industrial workers. Robotics is a potential solution that can help workers reduce their injury risks. This report outlines the development of a novel collaborative robot (cobot) that can help workers during lifting heavy objects and reduce the force needed from the workers. Design, control and testing of the proof of concept of the cobot are included in the development. A prototype has been successfully built which can assist workers during heavy object manipulation from one location to another location. The design can be broken down into two main categories including the design of a differential drive mobile base and a third arm that can provide partial object load support for the object. The design is based on the human-robot interaction for the cobot. The control is also separated into two main sections which are the control of the mobile base and the third arm. The mobile base control is dependent upon a 2D lidar detecting and following a user using a PD controller. The lifting using the third arm is controlled by the user by means of the joystick to provide partial object load support and the planar movements of the third arm is manually controlled by the user. The third arm is tested to determine the functionality proposed in the following sections of the report. The report concludes that there is room of improvement for the proposed cobot. Limitations of the cobot is discussed and future improvements are proposed.